The endocannabinoid system expression in the female reproductive tract is modulated by estrogen. Issue 174 (November 2017) - Maia, J.; Almada, M.; Silva, A.; Correia-da-Silva, G.; Teixeira, N.; Sá, S.I.; Fonseca, B.M.
Highlights: Uterine glands and lumen epithelium express all the endocannabinoid system members. Estradiol induces the expression of CB1, CB2 and anandamide-metabolic enzymes. Estradiol increases plasmatic anandamide levels. Estradiol decreases uterine PGE2 levels. Abstract: The endocannabinoid system (ECS) is involved in several physiological events that resulted in a growing interest in its modulation. Moreover, the uterine levels of anandamide (AEA), the major endocannabinoid, must be tightly regulated to create proper embryo implantation conditions. However, there are no evidences about the regulation of AEA in uterus by estrogen. Thus, the aim of this study is to elucidate whether estradiol benzoate (EB) and tamoxifen (TAM) administration to ovariectomized (OVX) rats can induce changes in the expression of cannabinoid receptors and AEA-metabolic enzymes in uterus by evaluating gene transcription and protein levels by qPCR, Western blot and immunohistochemistry. Moreover, the plasmatic and uterine levels of AEA and of prostaglandin E2 (PGE2 ) and prostaglandin F2 α (PGF2α ), the major cyclooxygenase-2 (COX-2) products, were determined by UPLC–MS/MS. The immunohistochemistry showed that cannabinoid receptors, as well as AEA-metabolic enzymes are mainly located in the epithelial cells of both lumen and glands and, to a lesser extent, in the muscle cells. Moreover, EB administration to OVX rats significantly increased CB1, CB2, NAPE-PLD, FAAH and COX-2 expression and transcription. These effects were absent in TAM and TAM + EB treatments showing that this response is estrogen receptor dependent. Additionally, although uterine levels of AEA remained unchanged in EB or TAM treated animals, they showed a rise with EB treatment in plasma. The latter also produced a decrease in uterine PGE2 levels. In summary, these data collectively indicate that the expression of ECS components, as well as, the AEA and PGE2 levels in rat uterus is modulated by EB. Thus, estradiol may have a direct regulatory role in the modulation of ECS in female reproductive tissues.